2011
DOI: 10.1177/1471301211416609
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency in Alzheimer's disease and Aphasia

Abstract: This study examined the impact of two neurological diseases on access to semantic knowledge and the status of semantic representations. Patients with Alzheimer's disease (AD) and Aphasia (APH) were compared with control groups using the supermarket fluency task. We measured several aspects: number of category names produced, number of categories sampled to produce the words, the number of words per category sampled, number of exemplars and kinds of errors recorded. Both AD and APH groups produced significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Considering that verbal fluency task can tap into lexical as well as executive processes, with exception of few studies (i.e., Arroyo‐Anlló et al . , Baldo et al . , Kiran et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that verbal fluency task can tap into lexical as well as executive processes, with exception of few studies (i.e., Arroyo‐Anlló et al . , Baldo et al . , Kiran et al .…”
Section: Introductionmentioning
confidence: 99%
“…Verbal fluency tasks are included in a broad range of aphasia assessments in both clinical and research studies. Despite its widespread use, there are only a handful of studies that have investigated both the quantitative (i.e., number of correct words) and qualitative (i.e., switching, clustering and/or temporal characteristics of recall) aspects of this task in aphasia (e.g., Adams et al 1989, Arroyo-Anlló et al 2011, Baldo et al 2010, Helm-Estabrooks 2002, Kiran et al 2014, Roberts and Le Dorze 1994, Sarno et al 2005. It is well established that PWA produce fewer exemplars than healthy controls but limited research exists with regard to the qualitative nature of the performance (Baldo et al 2010, Kiran et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Lexical characteristics, such as a word's frequency, age of acquisition, imageability, or name agreement, as well as the contexts in which items can appear, were all found to affect word retrieval on picture naming tasks in AD (e.g., Cuetos, Rodríguez-Ferreiro, Sage, & Ellis, 2012; Ivanova, Salmon, & Gollan, 2013). In addition, individuals with AD have been shown to retrieve fewer words on tasks of verbal fluency relative to age-matched healthy participants (e.g., Adlam et al, 2010; Arroyo-Anlló, Lorber, Rigaleau, & Gil, 2012; Haugrud, Crossley, & Vrbancic, 2011). A meta-analysis of 153 studies of verbal fluency with over 8000 patients suggested that the impairment was greater on the semantic than on the phonemic fluency task (Henry, Crawford, & Phillips, 2004).…”
mentioning
confidence: 99%
“…Similarly, the total number of information units recalled in the oral narrative task displayed the highest correlation with the vocabulary subtest of the WAIS-III. Although this can be explained by the fact that the vocabulary task also assesses verbal comprehension (Nascimento, 2004) and semantic memory (Arroyo-Anlló, Lorber, Rigaleau, & Gil, 2012;Rogers, Ivanoiu, Patterson, & Hodgers, 2006), it was expected that the oral narrative task from the MTL-BR would correlate most strongly with the total information contained in responses to the narrative discourse task from the MAC/brief MAC batteries. The number of picture elements recalled in the oral and written narrative tasks correlated most highly with the information subtest of the WAIS-III, as both tasks demanded semantic memory.…”
Section: Discussionmentioning
confidence: 99%